Characterization of commercially available ready-to-drink buko juice - Torres, Danilo Monserrata
The quality of ready-to-drink, commercially available buko juice was assessed. Procedures for preparing these juices were determined by visitation in places where they are produced. Physico-chemical, microbiological and sensory analyses were conducted for selected samples. Results indicated that the small scale producers do not use any type of preservatives in their products. The pH range of buko juice is from 4.8 to 5.3. Titrable acidity expressed as acetic acid was approximately 0.04%. Microbial count was about 1.83 x 10^3 to 8.2 x 10^4 cfu/mL. Based on the preference, the panelists wanted buko juice that has young, tender meat and has sweet-sour combination inherent in pure buko water. The kinetics of physico-chemical and microbiological changes was determined. This was done by monitoring the changes in some physico-chemical and microbiological changes stored at 6-10°C. The rate of change of titrable acidity is from 0.00005 to 0.00114 per unit of time. Soluble solids change at a rate of -0.0095 to -0.031 pero unit of time. Total plate count increases at rated between 0.076 to 0.097 log number of microorganism per unit of time. Yeast and mold counts on the other hand have rates of change from 0.1175 to 0.12 per unit of time. It lasted until undesirable change was noticed in the product. The shelf life of the buko juices was established as one and a half days to three days.